Questioning about Law Number 16 of 2019 concerning Marriage Dispensation in PA Kotamobagu - Misbahul Munir Makka; Rosdalina Bukido; Faradila Hasan (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
This research aims to show the results of the issuance of Law No. 16 of 2019 and the increasing application for marriage dispensation at the Kotamobagu PA. Underage marriage is a common thing in society. Many things are a factor in underage marriage, one of which is pregnancy outside of marriage and is considered to approve the proposed marriage dispensation. This research is field research located in PA Kotamobagu. The results obtained are that although the issuance of Law Number 16 of 2019, cases of underage marriages are even increasing. This case is evidenced in PA Kotamobagu. In 2020 the application for marriage dispensation was higher than the previous year. One of the reasons for submitting a marriage dispensation made by the community is a pregnant woman out of wedlock, so the judge must approve the proposed marriage dispensation. In other words, this law has no impact on suppressing the number of underage marriages, and the increased age limit has increased the dispensation for marriage.